2019
DOI: 10.1002/wdev.371
|View full text |Cite
|
Sign up to set email alerts
|

Hippo‐Yap/Taz signaling: Complex network interactions and impact in epithelial cell behavior

Abstract: The Hippo pathway has emerged as a crucial integrator of signals in biological events from development to adulthood and in diseases. Although extensively studied in Drosophila and in cell cultures, major gaps of knowledge still remain on how this pathway functions in mammalian systems. The pathway consists of a growing number of components, including core kinases and adaptor proteins, which control the subcellular localization of the transcriptional co‐activators Yap and Taz through phosphorylation of serines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 274 publications
(435 reference statements)
0
18
0
Order By: Relevance
“…The occurrence of diseases is often related to the dysfunction of key signaling pathways, such as the Hippo-YAP signaling pathway [ 23 , 24 ]. As we all know, the Hippo-YAP signaling pathway plays an important role in the development of the heart and participates in various physiological and pathological processes, including cardiovascular development, cardiac hypertrophy, angiogenesis, and regeneration [ 25 27 ]. Healen et al have confirmed that cardiac-specific knockout of SAV1 can block the Hippo-YAP/TEAD1 signaling pathway, significantly reduce the level of Yap phosphorylation, and lead to cardiac hypertrophy, which has also been verified in MST1/2 and LATS2 knockout mice [ 28 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of diseases is often related to the dysfunction of key signaling pathways, such as the Hippo-YAP signaling pathway [ 23 , 24 ]. As we all know, the Hippo-YAP signaling pathway plays an important role in the development of the heart and participates in various physiological and pathological processes, including cardiovascular development, cardiac hypertrophy, angiogenesis, and regeneration [ 25 27 ]. Healen et al have confirmed that cardiac-specific knockout of SAV1 can block the Hippo-YAP/TEAD1 signaling pathway, significantly reduce the level of Yap phosphorylation, and lead to cardiac hypertrophy, which has also been verified in MST1/2 and LATS2 knockout mice [ 28 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…12c-d), we found that RPE1 cells, as a non-transformed cell line, were susceptible to perturbations in core Hippo-YAP/TAZ signaling, in agreement with previous studies that aberrant activation of YAP is sufficient to drive uncontrolled cell growth of normal cell types 46 . However, in HeLa -the cancer cell line, in which Hippo pathway is believed to be dysregulated [47][48][49][50] , these selected genes were distributed in both central and peripheral YAP/TAZ signaling pathways 51 .…”
Section: Barbeko Enables Bidirectional Screens Of Non-transformed Cell Line Rpe1mentioning
confidence: 99%
“…In the absence of this phosphorylation, YAP is shuttled to the nucleus where it interacts with transcriptional co-factors, including TEADs 1-4, to regulate transcription of genes associated with cell proliferation, migration, and differentiation ( Varelas, 2014 ; Yu et al., 2015 ; Zhao et al., 2011 ; Pfleger, 2017 ). YAP interacts with several developmental pathways to regulate cell behaviors ( Piersma et al., 2015 ; van Soldt and Cardoso, 2020 ), including Wnt signaling to control cell proliferation and differentiation ( Gokey et al, 2018 ). In the developing airway, YAP directs basal cell fate decisions, with both nuclear and cytoplasmic YAP playing independent roles ( Mahoney et al., 2014 ; Lange et al., 2015 ; Zhao et al., 2014 ; van Soldt et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%